Variables Affecting Results of Sodium Chloride Tolerance Test for Identification of Rapidly Growing Mycobacteria - Conville, Patricia S. (American Society for Microbiology, 1998)
The sodium chloride tolerance test is often used in the identification of rapidly growing mycobacteria, particularly for distinguishing between Mycobacterium abscessus and Mycobacterium chelonae. This test, however, is frequently unreliable for the identification of some species. In this study we examined the following variables: medium manufacturer, inoculum concentration, and atmosphere and temperature of incubation. Results show that reliability is improved if the test and control slants are inoculated with an organism suspension spectrophotometrically equal to a 1 McFarland standard. Slants should be incubated at 35°C in ambient air and checked weekly for 4 weeks. Growth on control slants should be critically evaluated to determine the adequacy of the inoculum; colonies should number greater than 50. Salt-containing media should be examined carefully to detect pinpoint or tiny colonies, and colonies should number greater than 50 for a positive reaction. Concurrent use of a citrate slant may be helpful for distinguishing between M. abscessus and M. chelonae. Molecular methodologies are probably the most reliable means for the identification of rapidly growing mycobacteria and should be used, if possible, when unequivocal species identification is of particular importance.